2019
DOI: 10.2967/jnumed.118.222026
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTA-E[c(RGDfK)]2 PET Imaging of SHARPIN-Regulated Integrin Activity in Mice

Abstract: Shank-associated RH domain-interacting protein (SHARPIN) is a cytosolic protein that plays a key role in activation of nuclear factor κ-light-chain enhancer of activated B cells and regulation of inflammation. Furthermore, SHARPIN controls integrin-dependent cell adhesion and migration in several normal and malignant cell types, and loss of SHARPIN correlates with increased integrin activity in mice. Arginyl-glycyl-aspartic acid (RGD), a cell adhesion tripeptide motif, is an integrin recognition sequence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Increased expression of SHARPIN was reported in different types of cancers in human patients and appears to be associated with increased malignant behavior [ 36 41 ]. This may be in part due to its role in increasing neovascularization in cancer models [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of SHARPIN was reported in different types of cancers in human patients and appears to be associated with increased malignant behavior [ 36 41 ]. This may be in part due to its role in increasing neovascularization in cancer models [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, using a mouse B16 melanoma model, we demonstrated that [ 68 Ga]Ga-DOTA-Siglec-9 can be used to image tumor-associated inflammation. In that study, [ 68 Ga]Ga-DOTA-Siglec-9 could detect subcutaneous B16 melanoma tumors 7 days and 9 days after tumor cell inoculation (6). Moreover, blood vessels within melanoma tumors express VAP-1 in humans and mice (31,32).…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, VAP-1 mediates binding of T cells to sinusoidal endothelial cells in hepatocellular carcinoma, and adhesion of tumor-infiltrating lymphocytes, lymphokineactivated killer cells, and NK cells to tumor vasculature (3,4). We have previously shown that sialic acid-binding immunoglobulin-like lectin 9 (Siglec-9) is a VAP-1 ligand, and that a labeled Siglec-9 motif-containing peptide can be used for PET imaging of inflammation and B16 melanoma tumors (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The radiochemical purity was ≥ 99% and the molar activity was 18 ± 7.3 GBq/μmol ( n = 9). A non-targeted peptide [ 68 Ga]Ga-DOTA-E[c(RGEfK)] 2 , where E[c(RGEfk)] 2 = glutamic acid-[cyclo(arginyl-glycyl-glutamic acid- D -phenylalanine-lysine)], was used as a negative control as previously described ( 28 ).…”
Section: Methodsmentioning
confidence: 99%